Three‐dimensional printing CT‐derived objects with controllable radiopacity. (7th February 2018) - Hamedani, Borhan Alhosseini; Melvin, Alexa; Vaheesan, Kirubahara; Gadani, Sameer; Pereira, Keith; Hall, Andrew F.
Abstract: Purpose: The goal of this work was to develop phantoms for the optimization of pre‐operative computed tomography (CT) scans of the prostate artery, which are used for embolization planning. Methods: Acrylonitrile butadiene styrene (ABS) pellets were doped with barium sulfate and extruded into filaments suitable for 3D printing on a fused deposition modeling (FDM) printer. Cylinder phantoms were created to evaluate radiopacity as a function of doping percentage. Small‐diameter tree phantoms were created to assess their composition and dimensional accuracy. A half‐pelvis phantom was created using clinical CT images, to assess the printer's control over cortical bone thickness and cancellous bone attenuation. CT‐derived prostate artery phantoms were created to simulate complex, contrast‐filled arteries. Results: A linear relationship (R = 0.998) was observed between barium sulfate added (0%–10% by weight), and radiopacity (−31 to 1454 Hounsfield Units [HU]). Micro‐CT scans showed even distribution of the particles, with air pockets comprising 0.36% by volume. The small vessels were found to be oversized by a consistent amount of 0.08 mm. Micro‐CT scans revealed that the phantoms' interiors were completely filled in. The maximum HU values of cortical bone in the phantom were lower than that of the filament, a result of CT image reconstruction. Creation of cancellous bone regions with lower HU values, using the printer's infill parameter, was successful. Direct volume renderings of the pelvis and prostate artery were similar to the clinical CT, with the exception that the surfaces of the phantom objects were not as smooth. Conclusions: It is possible to reliably create FDM 3D printer filaments with predictable radiopacity in a wide range of attenuation values, which can be used to print dimensionally accurate radiopaque objects derived from CT data. Phantoms of this type can be quickly and inexpensively developed to assess and optimize CT protocols for specific clinical applications.